PENGARUH PELATIHAN BANTUAN HIDUP DASAR TERHADAP PENGETAHUAN DAN KESIAPSIAGAAN PENJAGA WISATA PADA KASUS KEGAWADARURATAN DI PANTAI SULAMADAHA KOTA TERNATE - Abd Hakim Husen; Ismail Rahman (NHM PRESS, 2022)
The important thing to be prepared for in order to prevent and minimize the risk of adverse impacts on victims is disaster preparedness. The type of research used in this research is this research using a Quasi-Experimental Design (Pseudo-Experimental) with a Pre-Post Without Control Group which was carried out in August 2022. The research sample was the community on the Sulamadaha tourist beach which involved 30 respondents who were selected randomly. randomized with respect to sample inclusion criteria. Bivariate analysis using the Wilxocon test is used for the effect of the independent variables on the dependent variable. All tests with a P-value (p)<0.05 were considered significant. The results showed that the level of knowledge of respondents before the intervention was as low as 100%. After being given basic life support training (BHD), most of them are highly knowledgeable with a frequency of 20 people (60%). Meanwhile, 7 people (30%) were moderate and 3 people (10%) were low. The statistical test results show that the p-value is <0.05. This means that there is an effect of providing interventions on the knowledge and preparedness of tour officers in providing basic life assistance (BHD) for victims.